2014
DOI: 10.1097/cin.0000000000000088
|View full text |Cite
|
Sign up to set email alerts
|

Practical Guidelines for Development of Web-Based Interventions

Abstract: Despite a recent high funding priority on technological aspects of research and a high potential impact of Web-based interventions on health, few guidelines for the development of Web-based interventions are currently available. In this article, we propose practical guidelines for development of Web-based interventions based on an empirical study and an integrative literature review. The empirical study aimed at development of a Web-based physical activity promotion program that was specifically tailored to Ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
0
6
0
3
Order By: Relevance
“…First, for effective recruitment, it would be critical to assess the characteristics of recruitment sites, either Web-based or offline. In addition, we highly recommend a combined use of Web-based and offline recruitment methods because recruitment only through the Internet may not work anymore due to changes in dynamics (eg, an increasing number of Internet frauds) [54]. …”
Section: Discussionmentioning
confidence: 99%
“…First, for effective recruitment, it would be critical to assess the characteristics of recruitment sites, either Web-based or offline. In addition, we highly recommend a combined use of Web-based and offline recruitment methods because recruitment only through the Internet may not work anymore due to changes in dynamics (eg, an increasing number of Internet frauds) [54]. …”
Section: Discussionmentioning
confidence: 99%
“…It is important to publish detailed descriptions of intervention development procedures in order to help prepare other researchers for the development process and so that reports of intervention trials can be interpreted properly (Barretto, Bingham, Goh, & Shope, 2011). Readers might also want to refer to alternative recent comprehensive approaches to web intervention development including the use of Intervention Mapping (Bartholomew, Parcel, Kok, Gottlieb, & Fernandez, 2011), instructional design (Hilgart et al, 2012), the PRECEDE model (Kattelmann et al, 2014), the process map of Elwyn and colleagues (2011), and the approaches of Barretto and colleagues (2011) and Chee and colleagues (Chee, Lee, Chee, & Im, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Using the criteria identified by Chee and associates, we evaluated the study in relation to meaningfulness, target population, focus, components, technological aspects, user logistics, and theoretical basis . 10 Individuals with SCI have severe limits in mobility but most use a computer. 18 Online forums for this population with SCI were evaluated prior to the study and found to be infrequently monitored, often with no activity for years on a site.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review of literature 10 Chee and colleagues indicated that little information is available on developing web-based interventions, and their team found only a few articles and book chapters on the subject. Based on a review of literature, they suggested guidelines for developing web-based interventions which include meaningfulness, target population, theoretical basis, focus, components, technological aspects, and user logistics.…”
mentioning
confidence: 99%
See 1 more Smart Citation